Development of ecological and phytogeographical mapping in the context of the landscape approach (on the example of Altai krai) - I. N. Rotanova; V. V. Gayda (Acta Biologica Sibirica, 2017)
Modern ecological phytogeographical cartography, in its conceptual and methodological aspects, is based on theoretical and practical knowledge of vegetation, accumulated in Russia and foreign countries. There is a number of summarizing publications which thoroughly describe the peculiarities of mapped vegetation. Considerable quantities of general and specific geobotanical maps have been created to solve various scientific and applied problems. Ecological and phytogeographical maps are of paramount applied significance and are used to evaluate the quality of the environment and perspective economic use of the territories. As a rule, the creation of ecological phytogeographical maps is based on a twofold approach: traditional ecological (bioecological) and ecological-geographical. The threat to phytodiversity is a danger of vegetation transformation and conditions under which the evolution and functioning of species can aggravate or stop. The following criteria were used to design the map of vegetation degradation and the degree of threat to phytodiversity on the territory of the Altai Krai.